Comparison of marginal fit between milled and three-dimensional printed polymethylmethacrylate prostheses for single crowns, anterior bridges, and pier abutment bridges: An in vitro study - Aman Merchant; Kiran Kumar Pandurangan; Amrutha Dinesh Shenoy; Deepak Nallaswamy; Pooja Nilesh Singh (The Journal of Indian Prosthodontic Society)
Aim: The purpose of this in vitro study was to compare the marginal fit of various three-dimensional (3D) printed and milled polymethylmethacrylate (PMMA) dental prostheses. Settings and Design: The study was conducted in an in vitro study setting. Materials and Methods: With a sample size of 45 for each fabrication method, this investigation compared the marginal fit of milled (Group 1) and 3D printed (Group 2) PMMA dental prostheses across different designs. The selection of samples was based on G*Power calculations. Tooth preparations were conducted on a typodont jaw set, followed by digital scanning and design processes. Computer-aided design and computer-aided manufacturing milling and 3D printing were employed for the fabrication of prostheses. The assessment of marginal accuracy at specific points was performed using a stereomicroscope. Statistical Analysis Used: Independent t-tests were used to evaluate marginal discrepancies between milled and printed prosthetic designs at specific tooth surfaces. Univariate analysis of variance assessed marginal discrepancies across prosthesis designs and fabrication methods, with the Tukey post hoc test for significantly different results (α =0.05). Results: Milled single crowns exhibited superior accuracy (61.50 ± 4.852 μ) compared to printed ones (65.74 ± 7.311 μ) (t = −1.868, P = 0.037). Similar trends were observed for other designs, emphasizing the impact of both prosthesis design and fabrication method on marginal fit. Notable discrepancies were found on the distal surfaces of the anterior bridge crossing midline design (t = −3.262, P = 0.003). Conclusion: Milled prostheses exhibited superior marginal fit as compared to 3D printed prostheses, with differences within clinically acceptable limits.